2017
DOI: 10.1039/c6ra28804a
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of hydrogen and hydroxyl radicals in water cages: a density functional theory study

Abstract: Radicals can be confined in water cages and exhibit similar structures and properties to their corresponding free forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…[31] The most popular hybrid functional has successfully demonstrated that the OH radical is encapsulated in water cages. [64] One important aim of the current study is to investigate the trend of the OH ⋆ stretching vibration from the gas phase up to liquid water because the currently only available MD simulation reveals only a band position from a power spectrum of one OH radical in liquid water. [24] A second aim is to examine the OH ⋆ stretching vibration of the OH radical in water clusters by using two different methods, namely the MLWF scheme and the radical Voronoi tessellation.…”
Section: Introductionmentioning
confidence: 99%
“…[31] The most popular hybrid functional has successfully demonstrated that the OH radical is encapsulated in water cages. [64] One important aim of the current study is to investigate the trend of the OH ⋆ stretching vibration from the gas phase up to liquid water because the currently only available MD simulation reveals only a band position from a power spectrum of one OH radical in liquid water. [24] A second aim is to examine the OH ⋆ stretching vibration of the OH radical in water clusters by using two different methods, namely the MLWF scheme and the radical Voronoi tessellation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of advantage to use dispersion corrected hybrid functionals, if liquid water is used in an AIMD simulation. [166][167][168][169] Regarding open-shell systems, it could be successfully shown in 2017 by Liu et al, 410 using DFT-D3 calculations, that hydroxyl radicals are encapsulated in water cages. Furthermore, a benchmark study of Tentscher and Arey, 411 about binding in radical-solvent binary complexes, revealed that the dispersion correction has a minor impact on their results.…”
Section: Introductionmentioning
confidence: 99%
“…41 The most popular hybrid functional has successfully demonstrated that the OH radical is encapsulated in water cages. 410 One important aim of the current study is to investigate the trend of the OH stretching vibration from the gas phase up to liquid water because the currently only available MD simulation reveals only a band position from a power spectrum of one OH radical in liquid water. 90 A second aim is to examine the OH stretching vibration of the OH radical in water clusters by using two different methods, namely the MLWF scheme and the radical Voronoi tessellation.…”
Section: Introductionmentioning
confidence: 99%
“…3. Both atomic radicals are stable indefinitely at 77 K, remaining trapped at some well-defined site within the hydrate structure (perhaps within empty 5 12 cages 65 ) as evidenced by a super-hyperfine interaction (Fig. 3).…”
Section: Nonlinear Photochemical Responsementioning
confidence: 99%